Most overweight and obese Indian children have nonalcoholic fatty liver disease - Sunil V. Pawar; Vinay G. Zanwar; Ajay S. Choksey; Ashok R. Mohite; Samit S. Jain; Ravindra G. Surude; Qais Q. Contractor; Pravin M. Rathi; Ravi U. Verma; Premlata K. Varthakavi (Annals of Hepatology, 2016)
Background and rationale. Nonalcoholic fatty liver disease (NAFLD) is the most common cause of pediatric liver disease in western countries. Its prevalence in Indian subcontinent is not well studied.Material and methods. In a school based cross sectional study we have screened overweight and obese children in the age group of 11 to 15 years for NAFLD. Ultrasonography, elevated serum transaminases, fibroscan were used for defining NAFLD. Dietary habits, blood pressure, serum lipid profile, blood counts and insulin resistance were recorded. The relation of fibrosis 4 score, pediatric NAFLD fibrosis index, aspartate transaminases to platelet ratio index (APRI) with fibroscan was evaluated.Results. Out of 616 students screened 198 were overweight and obese. Hundred students and their parents gave informed consent for the further evaluation. The prevalence of NAFLD was 62% in overweight and obese children. Fatty liver was found in 50 % students on ultrasonography, liver stiffness (≥ 6.1 Kilopascals) in 23% and raised alanine transaminase in 30%. Hypertension, dyslipidemia, diabetes mellitus and insulin resistance were seen in 6%, 18%, 2% and 66% students respectively. Systolic hypertension, serum triglyceride, aspartate transaminase, APRI was significantly higher in the NAFLD group. On binary logistic regression only systolic hypertension was an independent risk factor for NAFLD.Conclusion. In conclusion NAFLD is common in asymptomatic overweight and obese Indian children. Systolic hypertension is the only independent factor associated with NAFLD. Fibroscan has limited role for screening. We recommend screening for NAFLD in this high risk group with alanine transaminases and ultrasonography.